Peningkatan Motorik Kasar Anak Melalui Kegiatan Bermain Naik Turun Tangga di KB Miftahul Huda Candi Todanan Blora - Latifatus Sa’adah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to: (1) identify efforts to improve gross motor skills through stair climbing play activities at KB Miftahul Huda Candi Todanan Blora; (2) describe the supporting and inhibiting factors in the improvement of children's gross motor skills through this activity; and (3) determine the outcomes of gross motor skill enhancement through stair climbing play. The research uses a phenomenological approach with a qualitative descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and data verification. Triangulation of sources was employed to ensure data validity. The results show: (1) the introduction of stair climbing play involved explaining the rules and demonstrating the activity; (2) supporting factors included student motivation, facilities and infrastructure, human resources, children's enthusiasm, and physical condition, while inhibiting factors were fear, lack of independence, time limitations, insufficient movement stimulation, and gender differences; (3) the improvement of gross motor skills was evident as students were able to perform two activities simultaneously, such as climbing stairs while clapping hands or turning their bodies.